Yankee blitzkrieg : Wilson's raid through Alabama and Georgia - Jones, James Pickett (The University Press of Kentucky, 2000)
Yankee Blitzkrieg is the first comprehensive survey of Wilson's Raid, the largest independent mounted expedition of the Civil War. The Confederacy was reeling when Wilson's raiders left their camps along the Tennessee River in March 1865 and rode south. But there was talk of prolonged rebel resistance in the deep South using the agricultural and industrial facilties of a sweep of territory that ran from Macon to Meridian. That area had hardly been touched by the war, and in Columbus, Georgia, and Selma, Alabama, the South had two of its most productive industrial communities. Twenty-seven yea.